2022
DOI: 10.3390/jof8121280
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity of Candida parapsilosis Complex in Invasive Candidiasis at a Pediatric Tertiary Hospital: A 5-Year Retrospective Study

Abstract: Invasive candidiasis (IC) contributes to the morbidity and mortality of hospitalized patients and represents a significant burden to the healthcare system. Previous Brazilian studies have reported the presence of endemic Candida parapsilosis sensu stricto genotypes causing candidemia and clonal transmission involving fluconazole-resistant isolates. We performed a 5-year retrospective analysis of IC cases in a Brazilian tertiary pediatric hospital and conducted a molecular investigation of C. parapsilosis sensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The diversity of the genotypes detected in this study points to the possibility of numerous causes contributing to the occurrence of C. parapsilosis infections in Japan. In line with our findings, two recent studies in Brazil identified different C. parapsilosis genotypes among pediatric patients [31,32], but their results also confirmed whether these genotypes are phylogenetically related or not. Moreover, highly related genotypes have caused outbreaks of C. parapsilosis candidemia in neonatal intensive care units in the USA [33].…”
Section: Discussionsupporting
confidence: 92%
“…The diversity of the genotypes detected in this study points to the possibility of numerous causes contributing to the occurrence of C. parapsilosis infections in Japan. In line with our findings, two recent studies in Brazil identified different C. parapsilosis genotypes among pediatric patients [31,32], but their results also confirmed whether these genotypes are phylogenetically related or not. Moreover, highly related genotypes have caused outbreaks of C. parapsilosis candidemia in neonatal intensive care units in the USA [33].…”
Section: Discussionsupporting
confidence: 92%
“…Using STR (hereafter used instead of microsatellite), studies ( 4 , 6 , 8 , 16 18 ) have shown that outbreak or persistent clonal isolates of C. parapsilosis clustered according to being resistant or susceptible to fluconazole and that fluconazole-resistant isolates harbored the same mutation (i.e., Y132F) in the ERG11 -encoded azole-target fungal enzyme ( 2 ). No link between the presence of Erg11p mutation and STR-based clustering of C. parapsilosis isolates was shown elsewhere ( 11 , 22 ), suggesting that STR may not be discriminatory enough.…”
Section: Introductionmentioning
confidence: 91%
“…Together with some other Candida species (including C. albicans ), Candida parapsilosis sensu stricto , which belongs to the C. parapsilosis species complex (also including C. orthopsilosis and C. metapsilosis ), remains a leading cause of nosocomial bloodstream infection (BSI) worldwide ( 1 ). This species (hereafter referred to as C. parapsilosis ) continues to be dominant and/or associated with neonatal or pediatric hospital settings ( 2 ), particularly in Southern Europe (i.e., Mediterranean regions), Asia, and South America ( 3 11 ). Due to the propensity to form biofilm on medically implanted devices (including intravascular catheters) and the persistence in hospital environments ( 12 ), C. parapsilosis is increasingly involved in nosocomial outbreaks ( 13 19 ).…”
Section: Introductionmentioning
confidence: 99%